2009
DOI: 10.1187/cbe.07-10-0093
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Impact of Organic Chemistry Prerequisite on Student Performance in Introductory Biochemistry

Abstract: Curriculum design assumes that successful completion of prerequisite courses will have a positive impact on student performance in courses that require the prerequisite. We recently had the opportunity to test this assumption concerning the relationship between completion of the organic chemistry prerequisite and performance in introductory biochemistry. We found no statistically significant differences between average biochemistry grades or grade distribution among students with or without the organic chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 5 publications
5
13
0
1
Order By: Relevance
“…Entering GPA tended to be the variable most highly correlated to student grades in each course studied (Table 1), similar to previous results (Wright et al ., 2009; Rauschenberger and Sweeder, 2010). When each class was analyzed using our HLM, Entering GPA was the single best predictor, accounting for the most variance in all models (22.3–58.0%), followed frequently by Gender (1–3%).…”
Section: Resultssupporting
confidence: 90%
“…Entering GPA tended to be the variable most highly correlated to student grades in each course studied (Table 1), similar to previous results (Wright et al ., 2009; Rauschenberger and Sweeder, 2010). When each class was analyzed using our HLM, Entering GPA was the single best predictor, accounting for the most variance in all models (22.3–58.0%), followed frequently by Gender (1–3%).…”
Section: Resultssupporting
confidence: 90%
“…While students who completed a recommended prerequisite human physiology laboratory course earned significantly higher grades in a follow-up human anatomy course compared to students who did not enroll in the prerequisite, the effect was small (Table 3). This result is similar to those previously reported (Steele and Barnhill 1982, Canaday and Lancaster 1985, Wright et al 2009, Sato et al 2017.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have reported a lack of correlation. Wright et al (2009) examined performance in a biochemistry course and found that students performed equally well whether they had completed an organic chemistry prerequisite or not. Canaday and Lancaster (1985) found that there was no impact of undergraduate courses in biochemistry, vertebrate anatomy, histology, or embryology on the GPA of first-year medical students, courses that would presumably provide students with an advantage in medical school.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…Similar to our investigation, prior work outside CS has examined the relationship between course grades in prerequisites and followon courses, finding that prerequisite grades predict subsequent course grades [7,12,13,24]. Wright et al found that biochemistry course grades are not impacted by taking the recommended organic chemistry prerequisite, but did find a strong relationship between cumulative GPA and biochemistry course grade [29]. Similarly, we found a relationship between non-prerequisite non-major courses and subsequent course grade.…”
Section: Previous Work 21 Role Of Prerequisite Coursessupporting
confidence: 85%